OPTIMIZATION OF EXTRACTION PROCESS OF PUMPKIN SEED OIL CHARACTERIZED WITH HIGH PUFA CONTENT VIA DOUBLE RESPONSE SURFACE IN COMBINATION WITH MATLAB METHODOLOGY - XUE, S.; XIAO, X.; HUANG, Y. (Italian Journal of Food Science, 2020)
Box-behnken-double response surface optimization combined with Matlab analysis was used to optimize the extraction of Inner Mongolia pumpkin seed crude oil based on the relative content of polyunsaturated fatty acids (PUFA)(Y1) and crude oil yield (Y2). The influence of three single factors (solid-liquid ratio, extraction temperature, extraction time) of pumpkin seed was investigated. By the optimization of dual response surface analysis, the optimal extraction process parameter was as follows: solid-liquid ratio of 1:26.8 g/mL, extraction temperature of 30°C, extraction time of 2.5 h. On this condition, the relative content of PUFA was 43.54±0.14%, and the crude oil yield was 14.84±0.10 %, which showed no significant difference from theoretical value (p>0.05). In addition, by Matlab analysis, when the extraction time was taken as the lower level (C=2.5 h), Y1 was able to obtain larger theoretical values ( 45.8485%), however, when the temperature was taken as the higher level (C=3.5 h), Y2 can obtain larger theoretical values (17.0563%). When the extraction time was fixed as 2.5 h, and the solid-liquid ratio was within the range of 1:24-1:27 g/mL, extraction temperature was within the range of 30-32.5°C, Y1 and Y2 both can get the theoretical maximum value. The results of dual response surface optimization and matlab optimization are consistent. The combination on of the two methods can not only accurately obtain the best extraction scheme, but also more intuitively find out the reasonable process parameter interval of Pumpkin seed oil.